Quest for Idyllic Pleasure in Kincaid's Among Flowers: A Walk in the Himalaya - Upadhyay, Toya Nath (Humanities and Social Sciences Journal, 2021)
This study reads Jamaica Kincaid's travel text, Among Flowers: A Walk in the Himalaya (2005), as the author's quest for idyllic pleasure. Despite her identification as an anti-imperialist writer with her previous works, Kincaid turns towards simply inventing a garden in her hometown, Vermont in this text for aesthetic pleasure. Her arduous journey to the Eastern Himalayan landscape of Nepal for the quest of gardenworthy seeds to grow back in her private garden is intimately fraught with her passions of flowers. Engaging with the critical views of available critics such as Jill Didur, Pallavi Rastogi, Racia Anne Chansky and others on the book as well as concepts from travel writing theory, my study argues that Among Flowers: A Walk in the Himalaya bears Kincaid's search for idyllic pleasure of gardening rather than any imperialist or anti-imperialist underpinnings.